Embolization with NBCA for ruptured aneurysm located in the moyamoya-like collateral network associated with isolated middle cerebral artery occlusion - Lee, Cheol (Asian Journal of Neurosurgery, 2018)
Collateral vessel formation in moyamoya disease is a well-described phenomenon. However, the occurrence of unusual anastomosis pattern (moyamoya-like) associated with isolated middle cerebral artery (MCA) stenosis or occlusion has been reported very rarely and is not well known the relationship with aneurysm. We report a case of ruptured aneurysm treated with N-butyl cyanoacrylate (NBCA) located in moyamoya like collateral network with isolated MCA occlusion.
Keywords: Aneurysm; moyamoya; N-butyl cyanoacrylate